2015
DOI: 10.1080/02640414.2015.1022571
|View full text |Cite
|
Sign up to set email alerts
|

Footballers’ movement behaviour during 2-, 3-, 4- and 5-a-side small-sided games

Abstract: The aim of this study was to compare footballers' movement behaviour during 2-, 3-, 4- and 5-a-side small-sided games. Ten young professional players (age = 18.0 ± 0.67 years) participated in 3 bouts of each small-sided games for 6 min with 1 min of active rest between bouts. Positional data were collected using GPS system units and used to calculate the following variables: team centroid, distance between each player and own and opponent team centroids and distance between centroids. Approximate entropy was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
101
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 28 publications
7
101
1
3
Order By: Relevance
“…A larger number of players involved in SSCGs increased collective actions, loss of ball possession, and maintenance of the ball (36). Only one study maintained a proportional relationship between field dimensions and number of players (37). It was found that a greater number of players generated a greater distance from the players to the team center (37).…”
Section: Screeningmentioning
confidence: 98%
See 3 more Smart Citations
“…A larger number of players involved in SSCGs increased collective actions, loss of ball possession, and maintenance of the ball (36). Only one study maintained a proportional relationship between field dimensions and number of players (37). It was found that a greater number of players generated a greater distance from the players to the team center (37).…”
Section: Screeningmentioning
confidence: 98%
“…Of the articles analyzed, five manipulated the constraints on consecutive days (7,23,30,35,37), five carried out same-day manipulations, with an interval between constraints implementation using an activity/rest ratio of 1:1 (21,22,30,33,42), and the others did not mention how this methodological aspect was organised by investigators (12, 20, 26-29, 34, 36, 38, 39, 41, 44). Of the 24…”
Section: Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Sided games in soccer are understood to mean 5v5 (with or without a goalkeeper), 7v7 and 9v9 formats. The highest movement regularity found in 4v4 and 5v5 identified these formats as more adequate to promote team-related emergent and self-organised behaviours [12].Playing sided soccer has great benefits for players, especially in the learning stages [13]. The size of the field of play is smaller than in 11v11 and the rules are adapted accordingly (using smaller areas and goalposts, for example).…”
Section: Sided Games In Soccermentioning
confidence: 99%